تداولية الروابط الحجاجية في تفسير سورة النور عند فخر الدين الرازي - تيس علي; صويلح هشام (جامعة الوادي - University of Eloued, 2025)
تعّد الروابط الحجاجية أحد أهم العناصر التي يوظفها المتكلم لبناء نص متماسك من خلال ربط مكوناته بعضها ببعض قصد إنشاء الوظيفة الحجاجية الهادفة إلى التأثير في المخاطَب أو إقناعه. وقد حاولنا في هذا المقال استنباط وظائف الروابط الحجاجية من خلال بيان الأثر الذي تحدثه هذه الروابط في الكلمات والآيات التي ترد فيها...، وإذا كان علماء التفسير قد استندوا على الظواهر اللغوية عموما والبلاغية خصوصا فقد تطرقوا في كثير من المواقف إلى عامل الربط بين مجموع الحجج أو بين الحجج والنتائج مع بيان دلالاتها بغية الوصول إلى مقاصد القرآن وفهم معانيه. وفي هذه الدراسة توضيح لدلالة بعض الروابط الحجاجيةودورها البلاغي في "سورة النور" من خلال مُؤلّف "مفاتيح الغيب" للإمام فخر الدين الرازي، وقد سعينا إلى تطويع أدوات المنهج التداولي لبيان العلاقة البلاغية التي تربط الكلمات والآيات القرآنية بعضها ببعض. Argumentative links are considered one of the most important pillars of the communication process that links speech to each other with the aim of influencing the addressee. In this article, I have tried to trace one of the linguistic aspects at the rhetorical level in the Holy Qur’an, by explaining the impact that these links have on words and verses. In which it is contained..., and if the scholars of interpretation have relied on linguistic phenomena in general and rhetorical phenomena in particular, they have in many situations touched upon the factor of linking between the total arguments or between the arguments and results within the argumentative text, with an explanation of their implications in order to reach the purposes of the Qur’an and understand its meanings. In this study, there is an explanation of the implications of some argumentative links and their rhetorical role in “Surat An-Nur” through the book “Keys to the Unseen” by Imam Fakhr al-Din al-Razi. In this article, I have sought to adapt the tools of the pragmatic approach with analysis procedures to demonstrate the rhetorical relationship that links Quranic words and verses to each other. So that we can learn some of the secrets of this great book
مقال .مجلة علوم اللغة العربية وآدابها. مج 17. ع 02
Keywords: لروابط الحجاجية; السلّم الحجاجي; الحجة; النتيجة; سورة النور; The argumentative links; the Echelle argumentative; the argument; the result; Surat Al-Nur